PENGEMBANGAN VIDEO PEMBELAJARAN SENI TARI BERBASIS GERAK ALAM UNTUK SISWA KELAS III SEKOLAH DASAR - Nainggolan, Lenni Taniya; Zufriady, Zufriady; Guslinda, Guslinda (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
This study aims to develop media in the form of natural motion-based dance learning videos in the Cultural Arts and Craft lessons in elementary schools. The method used is research and development (R&D) using the Four-D model, which are the steps: Define, Design, Development, and Dissemination proposed by Thiagarajan. The R&D involved material experts, linguists and media experts as expert validators for the developed video. The data collection technique was in the form of a questionnaire. The data analysis technique used was to calculate the average score obtained from the material expert validator, language experts and media experts as well as the average score obtained from the product trial, namely the teacher and student responses. Based on the results of the video validation of natural motion-based dance learning that was developed, the criteria were very feasible with an average percentage of 87.57%. Meanwhile, for product trials, the teacher's response got a score of 91.02% and the student response got a score of 90.23% with a very good category. Based on the results of this study, it can be concluded that the natural motion-based dance learning video has met the criteria of being very feasible and very good, and it can be used in learning dance in recognizing motion in dance, especially for third grade students in elementary schools.